2016
DOI: 10.1038/srep23060
|View full text |Cite
|
Sign up to set email alerts
|

EMD in periodontal regenerative surgery modulates cytokine profiles: A randomised controlled clinical trial

Abstract: The enamel matrix derivative (EMD) contains hundreds of peptides in different levels of proteolytic processing that may provide a range of biological effects of importance in wound healing. The aim of the present study was to compare the effect of EMD and its fractions on the cytokine profiles from human gingival fibroblasts in vitro and in gingival crevicular fluid (GCF) in a randomized controlled split-mouth clinical study (n = 12). Levels of cytokines in cell culture medium and in GCF were measured by Lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Interestingly, we failed to reproduce the effects of EMD found in vitro in our clinical study. This is in line with a recent report by Villa et al, who found a similar discrepancy between cytokine levels in clinical samples of wound fluid after periodontal surgery and in vitro measurements [40]. However, in contrast to “clean” in vitro assays focusing on one particular cell type such as PDL fibroblasts, osteoblasts, or keratinocytes, a wide variety of different cell types and exudates will always contribute to GCF/WF samples, which may obscure the detectable effects of biological mediators on a given cell population within the periodontal wound.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, we failed to reproduce the effects of EMD found in vitro in our clinical study. This is in line with a recent report by Villa et al, who found a similar discrepancy between cytokine levels in clinical samples of wound fluid after periodontal surgery and in vitro measurements [40]. However, in contrast to “clean” in vitro assays focusing on one particular cell type such as PDL fibroblasts, osteoblasts, or keratinocytes, a wide variety of different cell types and exudates will always contribute to GCF/WF samples, which may obscure the detectable effects of biological mediators on a given cell population within the periodontal wound.…”
Section: Discussionsupporting
confidence: 93%
“…However, in contrast to “clean” in vitro assays focusing on one particular cell type such as PDL fibroblasts, osteoblasts, or keratinocytes, a wide variety of different cell types and exudates will always contribute to GCF/WF samples, which may obscure the detectable effects of biological mediators on a given cell population within the periodontal wound. Further, in the study by Villa et al [ 40 ], conventional macro-surgical flap designs and suture materials were used instead of micro-surgical or minimally invasive techniques and materials, which may have negatively affected the parameters assessed for characterization of early wound healing. Similarly, the poor outcome of soft tissue healing in EMD/BCP sites in our study may have contributed to the lack of detectable effects of EMD on cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Emdogain ® (Straumann, Switzerland) is a commercial product containing a mixture of EMDs that promote periodontal tissue regeneration in the application at the root surface and have osteopromotive properties [ 58 , 59 ]. Furthermore, Emdogain ® enhances wound healing in the gingival tissue with reduced complications, such as inflammatory reaction and pain, even in skin wound healing [ 60 , 61 ]. In vitro and in vivo studies have shown that EMD reduces the secretion of chemokines and pro-inflammatory cytokines related to chemotaxis, angiogenesis, inflammation, and fibroplasia, and its effect is critical in early wound healing according to a clinical study [ 61 ].…”
Section: Therapeutics For Periodontal Wound Healingmentioning
confidence: 99%
“…After periodontal surgical trauma, cell-signaling protein molecules (e.g., growth factors, chemokines, or cytokines) and products of cellular activity (enzymes and adhesion molecules) are released in the wound-healing area. Levels of cytokines, chemokines, and angiogenic biomarkers within the gingival crevicular fluid and in periodontal wound fluid have been studied in clinical trials to assess the ongoing angiogenesis, connective tissue, and bone formation activities during wound-healing phases (inflammation, granulation tissue formation, and tissue neoformation/remodeling) [1, 2]. Morelli et al [3] evaluated changes of angiogenic markers in wound fluid after placement of a soft tissue autograft or of a living cellular construct for treatment of mucogingival defects.…”
Section: Introductionmentioning
confidence: 99%